Factors Associated with Marketing of Branded Generic Drugs: A Study on Possible Strategies in the Indian Pharmaceutical Market - Umesh Chandra; Shwetha G. S. (Contemporary Research in Business, Management and Economics Vol. 8, 2024)
The pharmaceutical industry in India is quite competitive, and a company’s ability to succeed depends on its research and development capabilities. There is plenty of room for both bigger and smaller businesses to concentrate on the branded generic medication industry for the creation of prescriptions. As all the firms in this area sell the same medication and offer similar performance, there is little room for product uniqueness. As a result, businesses place a lot of emphasis on other aspects of brand identity. Thirteen key parameters that can affect the prescription generation of branded generic medications. For this purpose data was collected from 107 clinicians. After that, a factor analysis was performed to identify further contributing factors. It was discovered that physicians write prescriptions in response to two sets of factors: those linked to the firm and those related to the environment. When drafting the prescription, it was discovered that elements linked to the corporation had a greater impact on brand memory than factors related to the environment.